PECULIARITIES OF HEART RATE VARIABILITY INDICATORS IN TRACK-AND-FIELD ATHLETICS WITH MESOMORPHIC SOMATOTYPE - Sarafinjuk, L.A.; Syvak, A.V.; Radyoha, R.V.; Sarafinjuk, P.V.; Matseyko, I.I. (World of Medicine and Biology, 2020)
Disruption of autonomic-vegetative homeostasis is a direct path to the sports, especially cardiac, pathology appearance. Membership of the mesomorphic somatotype does not reduce the differences in the magnitude of cardiointervalographic indices between groups of athletes and non-athletes. We established a certain imbalance in the regulation of heart rhythm of athletes. According to the results of spectral indices, parameters of variational pulsometry and vegetative homeostasis ambiguous data were obtained, characterizing the influence on the athletes of the parasympathetic and sympathetic borders, which indicates the adaptation-regulatory mechanisms tension on them.